CONSUMPTION MODELS AND THEIR ROLE IN SHAPING THREATS TO GLOBAL FOOD SECURITY - Androshchuk, Ilona (Public Management and Policy, 2025)
The article examines the interrelation between urbanization, globalization, and the transformation of consumption models, which have a direct impact on the state of global food security. It is shown that the rapid growth of urban populations, lifestyle changes, rising income levels, and the development of digital trade platforms have shifted demand from traditional local products to industrially processed mass-produced goods. This trend increases the resource load on agricultural systems, provokes higher consumption of energy-intensive products, and contributes to the reduction of biodiversity. It is emphasized that urbanization creates spatial disparities in access to fresh and safe food, while the standardization of dietary models leads to the loss of cultural diversity in diets and increases national dependence on global supply chains. It has been established that globalization processes generate new risks of food vulnerability through the concentration of production in the hands of transnational corporations controlling a significant share of the world food market. The study highlights that these changes have economic, social, and environmental consequences, including growing food inequality, rising food waste, and the threat to national food sovereignty. The necessity of developing new approaches to food system management is substantiated - those that combine the principles of sustainable development, ecological balance, and social responsibility. The concept of “smart consumption” is proposed as the foundation for transitioning to more resilient production and consumption models that ensure balanced food system development and strengthen global food security. Particular attention is paid to the role of public policy in supporting local food initiatives, stimulating short supply chains, and enhancing consumer food literacy. It is noted that the synergy of government regulation, corporate responsibility, and consumer awareness may become a key factor in shaping a new paradigm of food stability. The results obtained have practical value for the development of sustainable agricultural strategies and the improvement of national food security policies.